The Recruitment Model of Metabolic Evolution: Jasmonate-Responsive Transcription Factors and a Conceptual Model for the Evolution of Metabolic Pathways - Shoji, Tsubasa (Frontiers in Plant Science, 2019)
Plants produce a vast array of structurally diverse specialized metabolites with various biological activities, including medicinal alkaloids and terpenoids, from relatively simple precursors through a series of enzymatic steps. Massive metabolic flow through these pathways usually depends on the transcriptional coordination of a large set of metabolic, transport, and regulatory genes known as a regulon. The co-expression of genes involved in certain metabolic pathways in a wide range of developmental and environmental contexts has been investigated through transcriptomic analysis, which has been successfully exploited to mine the genes involved in various metabolic processes. Transcription factors are DNA-binding proteins that recognize relatively short sequences known as cis-regulatory elements residing in the promoter regions of target genes. Transcription factors have positive or negative effects on gene transcription mediated by RNA polymerase II. Evolutionarily conserved transcription factors of the Apetala 2/Ethylene Response Factor (AP2/ERF) and basic Helix-Loop-Helix (bHLH) families have been identified as jasmonate (JA)-responsive transcriptional regulators of unrelated specialized pathways in distinct plant lineages. Here, I review the current knowledge and propose a theoretical model for the evolution of metabolic pathways, the “recruitment theory of metabolic evolution”. According to this theory, structural genes are repeatedly recruited into regulons under the control of conserved transcription factors through the generation of cognate cis-regulatory elements in the promoters of these genes. This leads to the adjustment of catalytic activities that improve metabolic flow through newly established passages.